Sistem Irigasi Tetes Otomatis untuk Tabulampot di Halaman Rumah Berbasis Mikrokontroler - Christian Halim, Daniel; Kusmadi, Kusmadi; Aprianti, Ine (LPPM Universitas Sangga Buana, 2025)
Family food security can be improved through the cultivation of Fruit Plants in Pots (Tabulampot) in home gardens. However, watering plants often becomes a challenge due to limitations in time, labor, and water usage efficiency. This study aims to develop an automatic drip irrigation system based on a microcontroller that can simplify plant care and optimize water usage. The system uses the NodeMCU8266 microcontroller, a Real-Time Clock (RTC) module, a relay, and a 12V water pump to control automatic watering based on a preset schedule. System testing shows that the relay operates effectively, controlling the pump to turn on for 2 minutes and off for 2 minutes according to the schedule programmed via the RTC. All components function stably without issues, and the system is effective in supporting water usage efficiency, especially in areas with limited water resources. The results of this study demonstrate that this automatic irrigation system provides a practical solution for time-based irrigation, which can be applied to Tabulampot cultivation. The system also opens opportunities for further development to improve its effectiveness and flexibility in home-based agricultural applications.